2017
DOI: 10.1111/lam.12710
|View full text |Cite
|
Sign up to set email alerts
|

A medicinal herbCassia alataattenuates quorum sensing inChromobacterium violaceumandPseudomonas aeruginosa

Abstract: Present study demonstrates the quorum sensing inhibitory activity of metabolites from Cassia alata, an important medicinal herb which is commonly used worldwide in the treatment of infections caused by microorganisms. An extract prepared from the leaves of the plant showed activity against quorum sensing in Chromobacterium violaceum and was also effective against attenuating the quorum sensing controlled virulence factors in Pseudomonas aeruginosa. Activity is attributed to the rich flavonoid composition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
3
14
0
3
Order By: Relevance
“…These results show that PMME affect the QS system in C. violaceum ATCC 12472 and C. violaceum CV026, since these strains have reduced violacein production. Similar results for violacein inhibition have been observed with fruit extracts (Oliveira, Rodrigues, Bertoldi, Taylor, & Pinto, ; Rodrigues, Oliveira et al., ; Rodrigues, Zola et al., ; Truchado et al., ; Vattem et al., ), medicinal plants (Rekha, Vasavi, Vipin, Saptami, & Arun, ; Vandeputte et al., ), and spices (Alvarez et al., ; Choo, Rukayadi, & Hwang, ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…These results show that PMME affect the QS system in C. violaceum ATCC 12472 and C. violaceum CV026, since these strains have reduced violacein production. Similar results for violacein inhibition have been observed with fruit extracts (Oliveira, Rodrigues, Bertoldi, Taylor, & Pinto, ; Rodrigues, Oliveira et al., ; Rodrigues, Zola et al., ; Truchado et al., ; Vattem et al., ), medicinal plants (Rekha, Vasavi, Vipin, Saptami, & Arun, ; Vandeputte et al., ), and spices (Alvarez et al., ; Choo, Rukayadi, & Hwang, ).…”
Section: Resultssupporting
confidence: 67%
“…production. Similar results for violacein inhibition have been observed with fruit extracts (Oliveira, Rodrigues, Bertoldi, Taylor, & Pinto, 2017;Rodrigues, Zola et al, 2016;Truchado et al, 2012;Vattem et al, 2007), medicinal plants (Rekha, Vasavi, Vipin, Saptami, & Arun, 2017;Vandeputte et al, 2010), and spices (Alvarez et al, 2014;Choo, Rukayadi, & Hwang, 2006).…”
Section: Food Microbiology and Safetysupporting
confidence: 74%
“…On the other hand, plants were found to synthesize compounds that interfere with bacterial QS (Venturi and Fuqua, 2013). It has been shown that mixtures of plant-derived compounds, including extracts (Biancalani et al, 2016;Tiwary et al, 2017), macerates (Ferluga et al, 2007;Subramoni et al, 2011;Rekha et al, 2017) and exudates (Teplitski et al, 2000;Gao et al, 2003;Nievas et al, 2017) interfere with bacterial QS mechanisms. Insight is now being gained into the nature of plant-derived QS modulating compounds that include flavonoids, phenolic acids and terpenoids (Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…b-Glucosidase (EC 3.2.1.21) is an enzyme that catalyzes the hydrolysis of glycosidic bonds for the release of glucose from cello-oligosaccharides and other glucosides linked by b-glucosidic linkages [1]. b-Glucosidase has been widely applied in various biotechnological processes, including the degradation of cellulosic agricultural residues to produce fuel ethanol [2] and aromatic compounds [3], to enhance the aroma in wine and tea [4,5], and in the bioconversion of isoflavone glycosides to aglycones [6]. However, the high cost of recovery of enzymes for repeated applications is a limitation to the wide application of b-glucosidase.…”
Section: Introductionmentioning
confidence: 99%